Analisis Partisipasi Mahasiswa/Mahasiswi Dalam Memajukan Koperasi Mahasiswa di Universitas Medan Area - Gabe Erdiana Sagala; Rypho Delzy Perkasa (FKIP, Universitas Palangka Raya, 2023)
Students need expertise that is in accordance with their interests and talents, therefore it is necessary to have a place that can accommodate them in developing their talents and interests, one of which is with student cooperatives. The purpose of this study was to find out the analysis of the lack of student participation in advancing student cooperatives at Medan Area University. This research is a type of descriptive analysis research. Data collection techniques used were interviews, observations, and literature studies from several related journal sources. Based on the research results of the analysis it was found that there were several factors that hindered the lack of interest of local students in cooperative activities on the campus including: activities held often collided with lecture activities, lack of interest from members in participating in activities, lack of knowledge from members regarding cooperatives, and the occurrence of differences in views between students regarding kopma so that it has an impact on student participation